Energy utilisation in selected industrial sectors in South Africa - Huggett, Anthony Court (Energy Research Centre, 2016)
This thesis presents tha findings of an investigation into the use of energy, between the years 1975 and 1984, in five of the major energy-intensive industries in South Africa. Energy use in all economic sectors, from 1964 to 1974, was surveyed in the report "Energy Utilisation in South Africa", published by the Department of Planning and the Environment in 1978. As this report showed the major primary industries to be the largest single users of energy in South Africa, it was decided to isolate a number of major energy-intensive industries for investigation in this study. The 1979 Census of Manufacturing showed five industrial sectors to have consumed 41% by value of the total industrial energy consumption in that year, and it is those with which this thesis is concerned. The five industries are: The Structural Clay Products Industry, The Portland Cement Industry, The Glass Making Industry, The Iron and Steel Industry, The Pulp and Paper Industry.